Towards Greenhouse Gas Mitigation: Novelty in Heterogeneous Catalysis - Khan, Wasim (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book has focused on novel developments and advancements in the field of heterogeneous catalysis with the aim of greenhouse gas reduction. The book determines whether carbon dioxide is a crisis or an opportunity, as well as its conversion into useful products such as synthesis gas. Moreover, the selective catalytic removal of nitrogen oxides is also presented.